Antifungal property of chili, shallot and garlic extracts against pathogenic fungi, Phomopsis spp., isolated from infected leaves of para rubber (Hevea brasiliensis Muell. Arg.) - Sittisart, Patcharawan; Yossan, Siriporn; Prasertsan, Poonsuk (Agriculture and Natural Resources, 2017)
The aim of this study was to evaluate the antifungal property of extracts of chili, shallot and garlic (local varieties in Sisaket, Thailand) against pathogenic fungi, Phomopsis spp., which were isolated from infected leaves of para rubber (Hevea brasiliensis Muell. Arg.). Seven isolates of Phomopsis spp. namely Phomopsis sp. SSK1.1, SSK1.2, SSK3.1, SSK4.1, SSK5.1, SSK5.2 and SSK7.1 were identified on the basis of morphological characteristics. Fresh plants were extracted with water to obtain crude extracts and their antifungal properties were tested on potato dextrose agar (PDA) media. The study demonstrated that increasing the concentrations (20%, 40%, 60% or 80%) of the chili extract exhibited a dependent increase in the inhibitory level on mycelial growth of Phomopsis spp. SSK3.1, SSK4.1 and SSK5.2. The inhibitory level on mycelial growth of shallot extract also increased in a dose-dependent manner in all isolates of Phomopsis. The garlic extract had significant inhibition on the growth of all isolates with complete inhibition at 80% concentration. The highest levels of percentage inhibition of mycelial growth were with garlic extract followed by shallot and chili extracts, respectively. The study also showed that these plant extracts contained some polyphenols (apigenin, gallic acid, catechin, quercetin, kaempferol and tannic acid) which are well-known compounds possessing antifungal activity. Therefore, it is possible that the antifungal properties of these plant extracts were partly due to these polyphenols or unknown active compounds which could not be analyzed in this study. Collectively, these results suggest that local varieties of both shallot and garlic possess strong antifungal properties.